The Influence of Workplace Incivility on Innovative Work Behavior: Mediating Effect of Employee Engagement and Moderating Effect of Emotional Intelligence (Journal of Asian Development Studies, 2024)
Workplace incivility is a common problem in academic intuitions, leading to deviant behaviours between both academic and non-academic staff members that have a robust significant impact on employees' behaviours towards organizations. Workplace incivility can stifle employee creativity. This study explores how employee engagement mediates this adverse effect and how emotional intelligence moderates the relationship between incivility and engagement. Drawing on the Conservation of Resources (COR) theory, we propose that incivility depletes employee resources, hindering innovative work behaviour. We hypothesize that high emotional intelligence buffers the negative impact of incivility on engagement, ultimately promoting innovative behaviour. Using data from faculty in Pakistani higher education institutions, we analyze the proposed model with PLS and SPSS software. Our findings confirm that workplace incivility reduces innovative work behaviour, but employee engagement weakens this adverse effect. Additionally, emotional intelligence strengthens the positive influence of engagement on innovative work behaviour. The study concludes with a discussion of implications for theory and practice, including future research directions.